2002
DOI: 10.1262/jrd.48.371
|View full text |Cite
|
Sign up to set email alerts
|

Factors Leading to Endometritis in Dairy Cows in Egypt with Special Reference to Reproductive Performance.

Abstract: Abstract. The incidence of endometritis and risk factors between herds and between breeds and its effect on the subsequent fertility of cows may differ among countries. It is therefore necessary to study the etiology of endometritis in these different circumstances. This work was carried out on 190 Holstein Friesian cows (2.5-13 years old) belonging to El-Salhia Agriculture project (Ismailia Province, Egypt) during the period from January 1996 to April 1997. The incidence of endometritis was 22.4%, and the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
14
0
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 6 publications
9
14
0
10
Order By: Relevance
“…The incidence of postpartum endometritis in this study (36.6%) was similar to those reported by Markusfeld [30] and Heuwieser et al [31], but the incidence w as higher than some previously reported rates (16.9-22.4%; [1,23,32]) and lower than the rate (61.6%) reported by Gilbert et al [15]. The different incidence rates of endometritis in these studies might be explained by the different diagnostic methods employed, different times of endometritis detection, different characteristics of the cows, or varied herd management practices [8,23,31,33].…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of postpartum endometritis in this study (36.6%) was similar to those reported by Markusfeld [30] and Heuwieser et al [31], but the incidence w as higher than some previously reported rates (16.9-22.4%; [1,23,32]) and lower than the rate (61.6%) reported by Gilbert et al [15]. The different incidence rates of endometritis in these studies might be explained by the different diagnostic methods employed, different times of endometritis detection, different characteristics of the cows, or varied herd management practices [8,23,31,33].…”
Section: Discussionsupporting
confidence: 89%
“…In India, the incidence of uterine infection was reported to range from 9.66% (Kumari et al, 2016) to 30% (Rao & Sreemannarayana, 1983) in buffaloes. Other reports indicate that the incidence of endometritis was 22.4% in Egyptian buffaloes (Ghanem et al, 2002) and 33.2% in Iranian buffaloes (Moghami, Saiyari, Mayatri, & Sharma, 1996). Controlled studies in cattle, based on the cytobrush cytology, indicate that SE is a problem in dairy herds.…”
Section: Discussionmentioning
confidence: 93%
“…Salpingitis, hydrosalpinx and pyosalpinx are common diseases in domestic mammals, especially cattle (McEntee 1990). Abnormalities of the buffalo cows reproductive organs had been reported in surveys in Iraq (Alwan et al 2001;Al-Fahad et al 2004), India (Rao and Sreemannarayana 1983;Sar et al 1996), Egypt (Ghaneem et al 2002) and Iran (Moghaddam and Mamoei 2004). The animals presented in all the above surveys did not included detailed pathological and bacteriological causes of certain abnormalities of the oviducts including salpingitis, hydrosalpinx and pyosalpinx.…”
Section: Introductionmentioning
confidence: 91%